Profile and Academic Performance of Special Admission Students: Analysis of a Pro-Inclusion Educational Policy in a Public University - Rodríguez-Garcés, Carlos René (2024)
Given the importance of promoting and articulating an educational system that guarantees equity and quality learning for students, this article aims to comparatively analyze the academic trajectories, the retention and performance, of university students admitted through special quotas and traditional routes. In terms of the methodology, data Data from 9,258 students participating in university admission processes from 2018 to 2021 were analyzed, with statistical modeling performed according to the traditional or special admission route. Regarding the results, the findings report that special admission students present better school performance and lower scores in university selection tests than their traditional counterparts, but in their academic trajectories, they exhibit better grades and adjusted dropout rates. The conclusions highlight the predictive importance of school performance, suggesting that vulnerability and poor quality of educational exposure do not necessarily constitute a disadvantage that conditions the university academic trajectory.